A National Health Service : Report of the Council of the B.M.A. to the Representative Body (1944)
1944 1944 1940s 11 pages 3 (ii) Freedom for people to choose their own medical advisers. (iii) Freedom for the doctor to pursue his professional methods in his own individual way. (iv) The personal doctor-patient relationship to be preserved, and the whole service founded on the "family doctor" idea. Some of the profession's more important criticisms of the White Paper proposals are set out below. SOME CRITICISMS Central Administration 21. The central administration arrangements proposed are unsatisfactory. The Minister of Health and his Ministry are still left responsible for a number of functions only remotely associated with health. For example, the Ministry of Health is left responsible not only for such problems of housing as are clearly and closely related to health but for supervising the activities of local authorities in the actual construction of houses. Housing is an important factor in health (as are wage levels). Their design and siting approved, their construction is a matter for architects, builders, and engineers rather than for the Ministry of Health. 22. There is another disadvantage. Housing will be an acute post-war problem, and inevitably Ministers of Health will for some years be greatly preoccupied with its political and financial implications. Responsibility to Parliament for a health service should be sufficient to occupy the energies of any one Minister and his Department. It should not be allowed to become, for political or other reasons, a secondary or subsidiary responsibility. 23. Under the Government's proposals health responsibilities are to remain diffused among a number of different Government Departments, including the Ministry of Health, the Board of Education, the Ministry of Labour, the Ministry of Pensions, the Post Office, and the Ministry of Fuel and Power. 24. One exclusion which the Government defends in the White Paper is scarcely justifiable — the exclusion of the industrial medical service. This is an employers' service, provided at the employers' expense. As a result it is common in the bigger and better factories, and much less common in the smaller works and factories where it is needed more. The factory is an important part of the worker's environment, and the medical supervision of the worker at the factory should therefore be linked with the supervision of his home environment, as part of the same health service. The industrial medical service is relatively new, and this linkage should be secured now. The Government's attitude in this is weak and illogical. Central Health Services Council 25. Side by side with the Ministry of Health there is proposed an advisory body, the Central Health Services Council, to represent medical practice and medical teaching, hospital organization, and other professional interests — a body primarily medical. The proposal conforms to the pattern of advisory bodies set up in recent years. Many of these advisory bodies have proved useless because they have not been allowed to become useful. They have been façades to protect Ministers rather than committees to advise them. The Association cannot accept, as an appropriate advisory body to present and make effective medical opinion at the centre, one which is to be appointed by the Minister and to report only through him. 26. This, the usual, method is wholly inadequate in its application to medicine. If a medical (or mainly medical) body is to express the view of the medical profession on medical matters, it should, so far as its medical members are concerned, be appointed by the profession itself and not by the Minister. The hand-picking of such an advisory body would make it useless. 27. Further, in the field of expert medical advice, both Parliament and public should be entitled to know what advice has been tendered and whether it has been accepted or not. Only such safeguards will secure that medical advice is effectively given. The Central Medical Board 28. The Association recognizes that in suggesting the Central Medical Board the Government intended to meet the known objection of general practitioners to enter into their contracts with local authorities. But the proposal to confer upon the Board two important powers has made this part of the White Paper a section to which the medical profession is most determinedly opposed. 29. The two powers are, first, the power to require practitioners intending to start afresh in public practice in any area to obtain in advance the approval of the Central Medical Board ; and, secondly, the power to require newly qualified practitioners desiring to take up public practice in a particular area to enter the public service whole-time where considered necessary. 30. Both these powers can be used by "negative pressure" to direct practitioners as to where they will practise in the public service and the type of public practice in which they shall engage. However they are described, they are a form of civil direction. The proposal to confer them is not made more attractive by the proposal that the Central Medical Board shall be composed mainly of doctors. The Association objects to their being conferred on any body — medical or lay or mixed. It recognizes that those who urge a planned economy for this country include as a part of their proposals some measures for the compulsory transfer of labour. The Board provides an illustration of the same trend of thought. 31. Errors of distribution of medical practitioners should be corrected by the process of attraction rather than that of compulsion. The Association is firmly opposed to the application of powers of compulsion either to doctors or to others. Indeed, they savour of a form of organization which this country has been exerting itself to oppose. Local Organization 32. At the periphery the kind of organization suggested in the White Paper is even more chaotic than at the centre. There will be more, not fewer, local authorities. The new type of local authority proposed — the Joint Health Authority — is to be concerned with the planning and administration of hospital and allied services, and with the planning of non-hospital services. No steps are proposed to ensure that either these joint health authorities or their committees will contain persons of knowledge and experience in these subjects. The planning done, and the Minister's approval obtained, the non-institutional services are to be administered by other authorities, the existing major local authorities. Health functions will thus be distributed between more and not fewer local authorities. 33. Health Centres, if established, will be administered by County and County Borough Councils, and hospitals by joint health authorities. Ante-natal centres will be administered by one authority, the maternity hospital by another, while the control of the midwives' service may be vested in yet another. Responsibility for the control of infectious disease will be assigned to one authority, and the provision of infectious diseases hospitals to another. Ultimately school medical inspection may be the responsibility of one authority, and school medical treatment the responsibility of another. The general practitioner will be in contract with the Central Medical Board or both the Central Medical Board and a major local authority. The consultant will be in contract with the individual hospital authority. The public health officer will be in contract with his individual local authority. In brief, what is proposed is fragmentation, not unification, of medical services. The Voluntary Hospital 34. The voluntary hospitals will, if the present proposals survive, be quietly but steadily submerged. Their contracts 36/H24/42